Métodos e técnicas de boa prática para implementação de um Network Operation Center (NOC) - Andreatta Junior, Ildebrando Tadeu (2011)
This project is meant to identify ways to implement a network management center, which features actors: computers, ISPs, network equipment and the like. Is contained in this project also the best practices and techniques to be used in a network management, also has the objective of managing SLAs, help identify gaps, and have a real-time control of all equipment contained in this management. Lecture clearly and simply the best technical implementation of a NOC, that in fact it manages to be reliable and agile. Today there are many tools and many ways to do this control, the aim of this paper is to show in detail and exemplified the various options for simple environments to more critical environments, showing the results obtained with each tool to prove that the study has the effect of show what the best tool versus technique for each type of environment.